2011
DOI: 10.1097/igc.0b013e3182021c1a
|View full text |Cite
|
Sign up to set email alerts
|

HERV-K Hypomethylation in Ovarian Clear Cell Carcinoma Is Associated With a Poor Prognosis and Platinum Resistance

Abstract: Methylation levels of HERV-K, HERV-E, and LINE-1 are decreased during OCCC multistep carcinogenesis. Moreover, HERV-K hypomethylation is a promising biomarker for predicting OCCC treatment response and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…The reason why LINE-1 hypomethylation only was a prognostic marker of GC is unclear at present. However, a similar example can be seen in Iramaneerat et al's study 43 in which a close correlation was found between human endogenous retrovirus K (HERV-K) and LINE-1 methylation levels in ovarian clear cell carcinoma tissue samples but HERV-K methylation level only was closely associated with clinical outcome. These results indicate that despite close correlation between LINE-1 and ALU or HERV-K methylation levels, certain tissue types or phenotypes of cancer are associated with certain transposable elements and support the hypothesis that genomewide hypomethylation in cancer might be promoted by multiple mechanisms, including generalized and locus-specific.…”
Section: Discussionmentioning
confidence: 84%
“…The reason why LINE-1 hypomethylation only was a prognostic marker of GC is unclear at present. However, a similar example can be seen in Iramaneerat et al's study 43 in which a close correlation was found between human endogenous retrovirus K (HERV-K) and LINE-1 methylation levels in ovarian clear cell carcinoma tissue samples but HERV-K methylation level only was closely associated with clinical outcome. These results indicate that despite close correlation between LINE-1 and ALU or HERV-K methylation levels, certain tissue types or phenotypes of cancer are associated with certain transposable elements and support the hypothesis that genomewide hypomethylation in cancer might be promoted by multiple mechanisms, including generalized and locus-specific.…”
Section: Discussionmentioning
confidence: 84%
“…38,39 In turn, epigenomes can be also responsible for modulating the response to environmental factors. [40][41][42][43][44][45][46]47 In the modulation of microbiota colonization, we theorize that epigenetically regulated mechanisms may be responsible for differential immune responses, the establishment of more or less permeable epithelial barriers, and bacterial metabolite processing, which will favor the colonization of particular bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of expression in ovarian somatic cells [11] together with decreased DNA methylation at L1 promoter region associated with the progression of cervical and uterus cancers [26] and poor prognosis in ovarian carcinomas [27] led us to investigate whether piRNA pathway genes could play a role in EOCs. In this study, we investigated the expression of PIWIL1 – 4 and MAEL in 25 EOC, 19 benign tumor samples, and 8 normal ovarian tissues.…”
Section: Introductionmentioning
confidence: 99%